KESEJAHTERAAN TENAGA PENDIDIK DAN KEPENDIDIKAN DI SDN BERTINGKAT NAIKOTEN KOTA KUPANG - Renhard Jepa; Maria Anjela Laka Silab; Hiwa Wonda; Oktafiani Diana Sibat (STKIP Subang, 2025)
This study aims to analyze the welfare of educators and educational staff, specifically how welfare, including appreciation, clear promotion paths, and supportive working conditions, impacts teacher motivation and performance. The research method uses in-depth interviews to obtain rich and contextual qualitative data from teachers and educational staff. The findings reveal that teachers who feel financially and psychologically well-being show high levels of motivation and professionalism, which in turn contribute significantly to the quality of learning. The appreciation given is not only in the form of economic compensation but also includes social and professional recognition as well as transparent and fair career paths that encourage teachers to continue developing their abilities. A conducive work environment and continuous training also play an important role in improving teachers' welfare and loyalty to educational institutions. The overall results of the study confirm that teacher welfare is a key factor in creating an effective and sustainable education system. This study recommends improving policies that prioritize teacher welfare in order to improve the quality of national education. These results are supported by experts such as Hutasuhut (2025), Sari (2020), and Moleong (2018), who highlight the importance of synergy between compensation, appreciation, and development.